Analisis Kemandirian Belajar Kimia Siswa Sekolah Menengah Atas se-Kota Mataram Berdasarkan Gender: Studi Deskriptif-Kuantiatif - Ermia Hidayanti; Yayuk Andayani (FKIP University of Mataram, 2025)
This study aims to analyze learning autonomy in chemistry among senior high school students in Mataram City, based on gender, using a descriptive-quantitative approach. This quantitative descriptive research employed a survey method utilizing a four-point Likert scale questionnaire consisting of 20 statements measuring six indicators: (1) learning initiated independently, (2) independence from others, (3) having a learning plan, (4) disciplined behavior, (5) active participation during learning activities, and (6) the desire to progress. The results of the independent samples t-test (p-value = 0.021 < 0.05) indicate a significant difference in self-regulated learning in chemistry between male and female students. The mean difference score of –2.54 shows that female students have higher learning autonomy in chemistry than male students. Particularly in the indicators of active participation during the learning process, the desire to improve, learning initiative, learning planning, and disciplined behavior. Despite the differences, both male and female senior high school students in Mataram City demonstrate good levels of learning autonomy in chemistry.